2019
DOI: 10.1016/j.neuron.2018.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Chromatin Modifier and Ephrin Signaling Genes in Vein of Galen Malformation

Abstract: Normal vascular development includes the formation and specification of arteries, veins, and intervening capillaries. Vein of Galen malformations (VOGMs) are among the most common and severe neonatal brain arterio-venous malformations, shunting arterial blood into the brain's deep venous system through aberrant direct connections. Exome sequencing of 55 VOGM probands, including 52 parent-offspring trios, revealed enrichment of rare damaging de novo mutations in chromatin modifier genes that play essential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 120 publications
1
61
0
Order By: Relevance
“…Recent literature further suggests that AGFs play a critical role in pathological vascular development in the brain. EphrinB2 is expressed in hemorrhagic AVM endothelium 14 , and sophisticated genetic screens have identified EphB4 mutations in some Vein of Galen Malformations and a small percentage of patients with capillary malformation-arteriovenous malformation syndrome [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature further suggests that AGFs play a critical role in pathological vascular development in the brain. EphrinB2 is expressed in hemorrhagic AVM endothelium 14 , and sophisticated genetic screens have identified EphB4 mutations in some Vein of Galen Malformations and a small percentage of patients with capillary malformation-arteriovenous malformation syndrome [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The inherited mutations showed incomplete penetrance and variable expressivity with carriers of the mutations often exhibiting cutaneous vascular abnormalities, consistent with a "two-hit" genetic mechanism. 104 The identified mutations in this study accounted for only approximately 30% of VoGM cases, suggesting further investigation is needed to elucidate a more complete picture of genetic driver mutations for formation of these lesions.…”
Section: Etiology and Geneticsmentioning
confidence: 87%
“…Unaffected parents and 2 healthy siblings of the proband were also genotyped for the c.830G>A EFNB2 mutation. Interestingly, the mother, who is the only carrier of the risk allele among all unaffected family members, is also the only family member exhibiting cutaneous vascular abnormalities, suggesting incomplete penetrance and variable expressivity of the mutation [16]. Overall, despite several EFNB2 mutations occasionally reported in various disorders discussed above, no clear association has been established statistically between EFNB2 and human diseases.…”
Section: Ephrinb2 Human Diseasesmentioning
confidence: 98%
“…Additionally, using an unbiased burden test considering all genes captured in human genome (n = 18,989), an independent WES study of 55 unrelated VOGM probands identified EPHB4, with 4 distinct variants, as the only loss of function (LoF) intolerant gene (pLI≥0.9) with genome-wide significant burden of rare damaging heterozygous mutations. Moreover, the Ephrin receptor signaling pathway was identified as the only over-represented pathway in cases but not controls using hypothesis-free pathway analysis, and genes (EPHB4, RASA1, EPHA4, EPHA6, ITGB1, ITSN1, and NGEF) contributing to the significance of the pathway map to a single experimentally supported interactome [16]. It is worth noting that in both studies, uncommon cutaneous CMs were reported in multiple VOGM probands as well as in EPHB4 mutation carriers not diagnosed with VOGM, but not in non-carriers from the same family.…”
Section: Ephb4 Human Diseasesmentioning
confidence: 99%